Structural Imaging-Based Biomarkers for Detecting Craving and Predicting Relapse in Subjects With Methamphetamine Dependence - Qi, Chang; Fan, Xiaobing; Foxley, Sean; Wu, Qiuxia; Tang, Jinsong; Hao, Wei; Xie, An; Liu, Jianbin; Feng, Zhijuan; Liu, Tieqiao; Liao, Yanhui (Frontiers in Psychiatry, 2021)
Abstract Background: Craving is the predictor of relapse, and insular cortex (IC) is a critical neural substrate for craving and drug seeking. This study investigated whether IC abnormalities among MA users can detect craving state and predict relapse susceptibility. Methods: A total of 142 subjects with a history of MA dependence completed structural MRI (sMRI) scans, and 30 subjects (10 subjects relapsed) completed 4-month follow-up scans. MA craving was measured by the Visual Analogue Scale for Craving. Abnormalities of IC gray matter volume (GMV) between the subjects with and without craving were investigated by voxel-based morphometry (VBM). The receiver operating characteristic (ROC) analysis was performed for the region-of-interest (ROI) of IC GMV to assess the diagnostic accuracy. Results: By comparing whole-brain volume maps, this study found that subjects without craving (n=64) had a significantly extensive decrease in IC GMV (family-wise error correction, p<0.05) than with craving group (n=78). The ROI of IC GMV had a significantly positive correlation with the craving scores reported by MA users. The ROC analysis showed a good discrimination (area under curve is 0.82/0.80 left/right) for IC GMV between the subjects with and without craving. By selecting Youden index cut-off point from whole model group, calculated sensitivity/specificity was equal to 78%/70% and 70%/75% for left and right IC, respectively. By applying the above optimal cut-off values to 30 follow-up subjects as validations, the results showed a very similar sensitivity (73-80%) and specificity (73-80%) for detecting craving state as model group. However, there was lower sensitivity (50-55%) and high specificity (80-90%) for predicting relapse susceptibility. Conclusions: Our study provides the first evidence that sMRI may be used to diagnosis the craving state in MA users based on optimal cut-off values, which could be served as MRI bio-markers and an objective measure of craving state.